The Utilization of Social Media as a Digital Marketing Tool for Strengthening the Local Economy in Kesugihan Village, Ponorogo - Rizal, Fitra; Izzati, Syafira Khairina; Mashadi, Naufal Hisyam (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the utilization of social media as a tool for digitizing the profile and promoting Kesugihan Village, Pulung District, Ponorogo Regency. The background of this research is the suboptimal use of social media at the village level, despite its significant potential to expand audience reach at a low cost. This study employs a descriptive qualitative method, with data collected through interviews, observations, documentation, and secondary sources. The findings indicate that Kesugihan Village possesses competitive advantages in the agricultural sector, micro, small, and medium enterprises (MSMEs), and tourism, particularly through activities at Sanggar Loka Sekar Wilis. The main challenges include low digital literacy and the absence of structured marketing strategies. Social media platforms, such as Instagram, Facebook, and TikTok, have proven effective in presenting village profiles, promoting local products, and attracting tourists, mainly when supported by training, mentoring, and the establishment of a digital promotion team. In conclusion, a consistent and well-directed social media strategy can expand market reach, enhance the competitiveness of local products, and foster sustainable economic development in the village.